Development and validation of HPLC method for determination of benidipine hydrochloride in lipid vesicles formulations - AL-Japairai, Khater; Syed Mahmood, .; Mohd Azmir, Arifin; Nadiya, Abdul Halim; Almurisi, Samah Hamed (Cosmos Scholars Publishing House, 2022)
In the current study, a novel high-performance liquid chromatographic method is being developed and validated to estimate benidipine hydrochloride in lipid-based pharmaceutical formulations including transfersome, ethosome, and transethosome. The chromatographic separation was accomplished on a ZORBAX Eclipse Plus C18 (4.6mm x 150mm) analytical column with a mobile phase consisting of a mixture of methanol and 50 mM phosphate buffer solution at a ratio of 70:30 (v/v). A standard calibration curve was used to quantitatively determine the medication at a UV wavelength of 237 nm. The limit of detection (LOD) and limit of quantitation (LOQ) were determined to be 0.005µg/ml and 0.015µg/ml, respectively. The relative standard deviation (%RSD) of the intra-day and inter-day studies for benidipine hydrochloride was less than 2%, and the percentage recovery of benidipine hydrochloride was found to be in the range of 98.57-100.27%. The method is specific, linear, accurate, precise, robust, and sensitive for its intended purpose, according to the results of the method validation. To determine the amount of benidipine hydrochloride and the effectiveness of drug entrapment in lipid-based formulated membrane like cell structures namely Transfersomes, Ethosomes, and Transethosomes the current method was successfully applied.